Mycophenolate mofetil therapy in scleritis: Analysis of seven cases in tertiary eye hospital in India - Monsudi, K F; Jyotirmay, B; Ayanniyi, A A (Journal of Chitwan Medical College, 2015)
To evaluate the effectiveness of immunomodulatory mycophenolate mofetil in the treatment of scleritis. A retrospective non comparative review of seven cases of scleritis managed with mycophenolate mofetil at a tertiary eye hospital. The following information was extracted from the patients folders; socio-demographics, causes, type of scleritis, duration of scleritis, previous treatment on before commencement of mycophenolate mofetil (MMF), any systemic association, visual acuity (VA) at presentation and at the last hospital visit, laterality of the scleritis and the side effects experienced during the use of mycophenolate mofetil.Two patients with anterior nodular and four patients with diffuse anterior scleritis were identified. The mean follow up was 6 months. Six patients had the same pre-treatment VA and one patient had improved VA. No patient reported any side effect. All the inflammations were controlled in all the patients and no case of relapsed during the usage of MMF was reported. And no patient needed any additional immmunosupressive agents.Mycophenolate mofetil appears to be an effective drug in the management of anterior scleritis. The absence of side effects following its use is remarkable. It holds promise to reducing the blinding complication of scleritis. A further study with large sample size may be required to confirm our findings. DOI: http://dx.doi.org/10.3126/jcmc.v5i1.12572